2019
DOI: 10.3390/genes10070485
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of the Sponge Suberites domuncula (Olivi, 1792) in the Presence of a Symbiotic Bacterium and a Pathogen Bacterium

Abstract: Sponges, which are in close contact with numerous bacteria in prey/predator, symbiotic and pathogenic relationships, must provide an appropriate response in such situations. This starts with a discriminating recognition of the partner either by a physical contact or through secreted molecules or both. We investigated the expression of the Toll-like receptor, Caspase 3/7, Tumor Necrosis Factor receptor-associated factor 6, Bcl-2 homology protein-2 and macrophage expressed genes of axenic sponge cells in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…It is also not yet known if Perforin-2 can breach bacterial membranes by itself or if it requires the assistance of other host proteins. Our review and evaluation of the in vitro systems reported to date raises significant doubts that Perforin-2 dependent killing was actually observed with recombinant protein ( 27 , 29 31 , 33 , 34 , 38 , 39 , 43 ). Our first major concern is that some researchers opted to purify the MACPF domain in the absence of the P2 domain ( 29 , 31 , 43 ).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…It is also not yet known if Perforin-2 can breach bacterial membranes by itself or if it requires the assistance of other host proteins. Our review and evaluation of the in vitro systems reported to date raises significant doubts that Perforin-2 dependent killing was actually observed with recombinant protein ( 27 , 29 31 , 33 , 34 , 38 , 39 , 43 ). Our first major concern is that some researchers opted to purify the MACPF domain in the absence of the P2 domain ( 29 , 31 , 43 ).…”
Section: Discussionmentioning
confidence: 90%
“…Nevertheless in recent years vertebrate studies have established that Perforin-2 has broad spectrum bactericidal activity that significantly limits pathogen proliferation and dissemination in vivo ( 15 , 19 , 26 , 52 54 , 57 , 72 , 90 ). There is also evidence to suggest that Perforin-2 functions similarly in invertebrates; although, such studies are hampered by the lack of animal and tractable cell culture models ( 27 , 28 , 30 , 31 , 33 , 38 , 39 ). The recent structural determinations of both mouse and human Perforin-2 polymers have further provided significant insight with regards to the mechanism(s) of pore formation ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hostmicrobiota interactions are based on the exchange of information, that comes from the microbial signal -host receptor interactions. This recognition lies in the host innate immune system, which plays a crucial role in animal-microbe crosstalk (Schmittmann et al, 2020;Ie Pennec and Gardères, 2019;Dierking and Pita, 2020). The host innate immune system includes a complex repertoire of immune receptors, so-called pattern recognition receptors (PRRs), that recognize the microbe associated molecular patterns (MAMPs) present in prokaryotes but absent in eukaryotes (Medzhitov and Janeway, 2002;Koropatnick et al, 2004).…”
Section: Host-mediated Recognition Of Symbiontsmentioning
confidence: 99%
“…2A. Some studies have also described receptor molecules in sponges, including pathogen‐recognition receptors (PRRs) and pathogen‐associated molecular patterns (PAMPs), which are well‐conserved molecular structures expressed by various pathogens (virus, bacteria, fungi, protozoans, helminths) (Hentschel et al ., 2012; Yuen et al ., 2014; Di Lorenzo, 2017; Pita et al ., 2018a; Le Pennec and Gardères, 2019).…”
Section: Introductionmentioning
confidence: 99%